2020
DOI: 10.1002/mrd.23424
|View full text |Cite
|
Sign up to set email alerts
|

Sperm chromatin condensation and single‐ and double‐stranded DNA damage as important parameters to define male factor related recurrent miscarriage

Abstract: The aim of the present work is to characterize the relationship between sperm protamine deficiency and single-and double-stranded DNA damage and to assess the diagnostic potential of chromomycin A3 (CMA3). For that purpose, semen samples from 90 human males with different clinical features were included (fertile donors, patients with recurrent pregnancy loss [RPL], and infertile patients). DNA condensation was analyzed by CMA3 and different types of DNA fragmentation were analyzed through the comet assay. A po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…On the other hand, the accumulation of CNVs/LOHs in ART-aborted fetuses might be just a parallel result but not a direct reason of the abortion. Evidences had shown that DNA damage in either oocytes [26][27][28][29] or sperms [30][31][32][33] could induce spontaneous abortion. So DNA damage can be the source of both CNVs/LOHs and abortion.…”
Section: Plos Onementioning
confidence: 99%
“…On the other hand, the accumulation of CNVs/LOHs in ART-aborted fetuses might be just a parallel result but not a direct reason of the abortion. Evidences had shown that DNA damage in either oocytes [26][27][28][29] or sperms [30][31][32][33] could induce spontaneous abortion. So DNA damage can be the source of both CNVs/LOHs and abortion.…”
Section: Plos Onementioning
confidence: 99%
“…Accordingly, our results evidenced lower chromatin condensation in viable than in non-viable sperm. However, while no study in the literature has simultaneously evaluated sperm viability and chromatin condensation, one could reasonably surmise that chromatin decondensation is higher in non-viable sperm due to their increased oxidative stress, as free radicals and DNA fragmentation were previously found to be positively correlated with sperm chromatin decondensation [ 15 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, many authors suggested the association of sperm DNA integrity with sperm quality and fertility in farm animals [9][10][11]. While sperm DNA integrity, assessed through different methods, is the most common genetic parameter used to predict male infertility in humans [8,12,13], different studies showed that sperm protamine content and protamine1/protamine2 ratio may also underlie infertility [14][15][16]. Although chromatin might also be contributing to fertilization success in livestock, given the relevance of nucleoprotein structure integrity [17][18][19], it has not been well-studied as a fertility biomarker [9].…”
Section: Introductionmentioning
confidence: 99%
“…The vacuoles were first described as nuclear craters or thumbprints, or DNA-free areas, in connection with no or low condensation of the sperm chromatin [ 29 , 31 , 34 , 35 , 36 ]. Hence, deselecting sperm with chromatin condensation abnormalities could improve pregnancy rates and decrease miscarriage rates [ 33 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ].…”
Section: Introductionmentioning
confidence: 99%